The effect of Kahoot! learning media on learning outcomes of German language students - Samuel Jusuf Litualy; Henderika Serpara; Eldaa Crystle Wenno (Journal of Education and Learning (EduLearn), 2022)
This study aimed to determine the effect of the Kahoot! educational game learning media on German language students' learning outcomes in the Sprechfertigkeit 2 course. The sample of this study consisted of 37 students. The test instruments were given during the pretest and posttest. The data were processed and analyzed by the SPSS program. The Cronbach Alpha validity test showed that the study had high validity (0.764). The instrument normality test shows the value of p more than alpha (0.05). The statistical test resulted that the value of t-test=631 (more than t-table=398). The study revealed a significant effect of the Kahoot! educational game learning media on learning outcomes of German students in Sprechfertigkeit 2.